A Study of The Epidemiology of Pre-Senile Cataract in Patients Attending Ophthalmic OPD– A Hospital-Based Study - Faruqui, Saba; Patel, Smita; Sthapak, Aditi; Jain, Rahul (Journal of Neonatal Surgery, 2025)
Pre-senile cataract, or opacification of the lens occurring before 50 years of age is a disease causing visual impairment in young individuals. There have been certain risk factors such as sunlight exposure, high myopia, diabetes mellitus, smoking and exposure to some drugs that are known to be associated with pre-senile cataract. Aims and Objectives: This study aimed determine the impact of socio-economic, environmental and systemic risk factors on the development of pre-senile cataract. Design: Prospective observational study Materials and methods: 180 patients with pre-senile cataract were studied. Patients between 20-50years of age who consented to the study were asked to respond to a questionnaire which covered their social, occupational, personal and medical history. A complete eye examination was done to determine presence and morphological type of cataract. Results: There were 99 (55%) females and 81(45%) males with pre-senile cataract. Posterior subcapsular was the most common type (58.8%). 33.8% cases had outdoor occupation followed by steroid intake (23.8%) and diabetes (22.2%). Conclusions: UV exposure (sunlight), steroid intake in some form, high myopia and diabetes were found to be some of the risk factors commonly found in these patients and their modification through health education and life-style changes could have an impact on the development of cataract. Key-words: Pre-senile cataract, risk factors, life-style. modification